2008
DOI: 10.1080/01676830802222811
|View full text |Cite
|
Sign up to set email alerts
|

Digital Photography as a Novel Technique of Measuring Ocular Surface Dimensions

Abstract: Digital ocular photography combined with computerized image analysis is a fast, easy to use, and reliable method of measuring ocular surface dimensions. In addition to ptosis surgery, this method can be used in other ocular surface studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Eye and skin areas within the goggle were determined via a pixel-counting method adapted from Koushan et al 81 A digital camera (Sony Cyber-Shot DSCH50, Tokyo, Japan) was used to capture three pictures of each subject (or the mannequin eye) in the primary (perpendicular) gaze position. While in a sitting position, the subject was asked to look straight ahead in a relaxed manner during photographing.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Eye and skin areas within the goggle were determined via a pixel-counting method adapted from Koushan et al 81 A digital camera (Sony Cyber-Shot DSCH50, Tokyo, Japan) was used to capture three pictures of each subject (or the mannequin eye) in the primary (perpendicular) gaze position. While in a sitting position, the subject was asked to look straight ahead in a relaxed manner during photographing.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Again, for the same reason, indirect measurements, such as the ratio of pupil height to the distance between the 2 canthuses (which has a constant value for each patient), were used in addition to direct measurements, such as the distance between the pupil and the upper eyelid or the orbital fissure distance. 12 The exposed OSA, which is another measurement method described by Koushan et al, 13 seems to be effective for the calculation of the conjunctival area, which is indirectly affected by ptosis. All of the distinctive measurement methods used in this study indicated that the brow elevation, obtained with the aid of botulinum A toxin in patients who had undergone frontal slinging, was achieved without the development of lagophthalmos in the upper lid.…”
Section: Discussionmentioning
confidence: 99%
“…The diagram is rapidly obtained and precisely outlines the lower palpebral border through the use of the pen tool in the software program, which we believe is superior to other selection tools previously used to obtain measurements in the ocular region. 10 In obtaining measurements from digital images, earlier investigators used a ruler taped to the patients' heads as a reference and calibration tool. 10 This method is cumbersome and may be difficult to implement routinely during office consultations.…”
Section: Discussionmentioning
confidence: 99%